2023
DOI: 10.1007/s00204-023-03529-w
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of acid sphingomyelinase as a potential target for therapeutic intervention in hepatic disorders: current scenario and anticipated trends

Abstract: Acid sphingomyelinase (ASMase) serves as one of the most remarkable enzymes in sphingolipid biology. ASMase facilitates the hydrolysis of sphingomyelin, yielding ceramide and phosphorylcholine via the phospholipase C signal transduction pathway. Owing to its prominent intervention in apoptosis, ASMase, and its product ceramide is now at the bleeding edge of lipid research due to the coalesced efforts of several research institutions over the past 40 years. ASMase-catalyzed ceramide synthesis profoundly alters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…The liver plays an important role in lipid metabolism, taking up free fatty acids, forming triglycerides and VLDL in addition to acting as a site for lipid storage. Lovric et al identified a positive correlation between serum concentrations of sphingomyelin with increased ectopic fat accumulation (including hepatic steatosis) [47,48]. In murine models it has been shown that sphingomyeline synthesis is activated in MASH, being related to hepatocyte pyroptosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…The liver plays an important role in lipid metabolism, taking up free fatty acids, forming triglycerides and VLDL in addition to acting as a site for lipid storage. Lovric et al identified a positive correlation between serum concentrations of sphingomyelin with increased ectopic fat accumulation (including hepatic steatosis) [47,48]. In murine models it has been shown that sphingomyeline synthesis is activated in MASH, being related to hepatocyte pyroptosis [49].…”
Section: Discussionmentioning
confidence: 99%
“…The liver plays an important role in lipid metabolism, taking up free fatty acids, forming triglycerides and VLDL in addition to acting as a site for lipid storage. Lovric et al identified a positive correlation between serum concentrations of sphingomyelin with increased ectopic fat accumulation (including hepatic steatosis) [51,52]. In murine models, it has been shown that sphingomyeline synthesis is activated in MASH, being related to hepatocyte pyroptosis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several antidepressants act as functional inhibitors of acid sphingomyelinase (FIASMAs): most of them are FDA-approved, characterized by low toxicity, and used for many therapeutic applications [94]. With regard to COVID-19, there is evidence of the use of FIASMAs as these antidepressants interfere with different steps of the SARS-CoV-2 life cycle by acting through the Cer system.…”
Section: Sphingolipids As Potential Therapeutic Targets In Sars-cov-2...mentioning
confidence: 99%